Optimization and validation of an ELISA using recombinant Toxoplasma gondii matrix antigen 1 for serodiagnosis of the infection (Mongolian Journal of Agricultural Sciences, 2015)
Toxoplasma gondii infection can be diagnosed directly by polymerase chain reaction (PCR), hybridization and isolation of parasites and indirectly with serological methods[4; 5; 18].Although all these tests have shortcomings, serological tests, particularly the enzyme-linked immunosorbent assay (ELISA), seem to be the most practical and economical. The crude antigen prepared from tachyzoites has been traditionally utilized for commercially serological detection kits. However the use of recombinant antigens can be alternative sources of antigens allowing better standardization of the tests and reducing the costs of production requires mass production of the parasite either from the peritoneal fluids of infected mice or from tissue cultures. In spite of the potential advantages of using recombinant antigens in serology tests, their sensitivities have not yet achieved perfect result; therefore, further research on new antigensis extremely desirable [10; 16; 17; 3]. In this context, the Toxoplasma gondii matrix antigen 1 (TgMAG1) known as 65-kDa protein abundantly expressed within the cyst and in the cyst wall surrounding the bradyzoites [15], has documented to be immunogenic during the infection with T. gondii in mouse model and promising reagent for serodiagnosis of toxoplasmosis in humans [15;12; 6]. However, its usefulness has not yet been confirmed in animal toxoplasmosis.In this study, the optimization and validation of E.coli-expressed rTgMAG1as ELISA antigen were describedMongolian Journal of Agricultural Sciences Vol.15(2) 2015; 56-60